Qualitative Choice and the Blending of Discrete Alternatives - Anas, Alex; Moses, Leon N. (The Review of Economics and Statistics, 1984)
This paper takes a fresh look at discrete choice theory by observing that decision makers can deliberately blend discrete alternatives within an extended planning honrzon. Multinomial logit and generalized probit models are developed and their properties examined. These are then estimated and compared to the traditional myopic model using the travel diaries of a sample of commuters from Seoul, Korea. The new models yield travel cost elasticities which are substantially lower than those of the traditional approach.